Weimar Germany : promise and tragedy - Weitz, Eric D. 1953- (Princeton Univ. Press, 2007)
'Weimar Germany' explores the great political and cultural innovations in Germany after World War I. Germans forged democratic institutions and the country's great talents developed new forms of expression that reflected modern, mass society.